Rightsizing untuk Keberlangsungan Hidup Organisasi - Achmad Sobirin; Fathul Himam (Jurnal Siasat Bisnis, 2009)
By utilizing action research approach, this paper discusses the process of how to extent organizational life using rightsizing program. Results indicate that the program, formerly, did not work smoothly. However, after the researcher make some changes in approaching parties involved, the program finally could work well and even get positive response from those parties. Final result of rightsizing program is the shifting paradigm in managing the aged organization from production oriented to maintenance oriented with HSE as a paradigm. Keywords: rightsizing, hidup organisasi, production-oriented, maintenance-oriented